Floral Color Variation in Drosera cistiflora Is Associated With Switches in Beetle Pollinator Assemblages - Johnson, Steven D.; von Witt, Caitlin G.; Anderson, Bruce (Frontiers in Plant Science, 2020)
Floral color shifts are thought to be one of the most common evolutionary transitions in plants, and pollinators are often proposed as important selective agents driving these transitions. However, shifts in flower color can also be related to neutral genetic processes or pleiotropy linked with selection via other biotic agents or abiotic factors. Here we ask whether abiotic factors or pollinators provide the best explanation for divergence in flower color among populations of the sundew Drosera cistiflora s.l. (Droseraceae). This species complex in the Greater Cape Floristic Region contains at least five distinctive floral color forms. Abiotic factors do not appear to play a significant role in color determination, as the forms are not specific to a single soil or vegetation type, sometimes co-occur in the same habitat, and maintain their color traits in common-garden and soil switching experiments. Instead, we found strong associations between flower color and the composition of pollinator assemblages which are dominated by hopliine scarab beetles. Pollinator assemblages show geographical structuring, both within and among color forms. This makes it difficult to dissect the roles of geography versus floral traits in explaining pollinator assemblages, but strong pollinator partitioning among color forms at sites where they are sympatric indicates that pollinators may select strongly on color. These results suggest that beetle pollinators are a significant factor in the evolution of D. cistiflora s.l. flower color.